Methodological approach on optimizing the speed of navigation to reduce fuel consumption and increase energy efficiency of the cruising ship - Radonja, Radoslav (Array, 2019)
Modern large cruise ships have great energy needs for different technological processes on board. The energy needs depend on the operating conditions and the required speed of the ship, and the high energy requirements usually mean high fuel costs. With the enforcement of international regulations aimed at reducing environmental pollution, various measures and procedures have been proposed to increase the energy efficiency of ships. This paper outlines method that can be applied to ships without installing new or modification of existing systems and will require somewhat increased attention of chief engineer during voyage and his close cooperation with the captain. Traditionally, the required speed of the ship will be determined by the length of the fairway divided by the time that is available for travel. Analyzing originally collected data from the cruising ship it was concluded that by optimizing the speed of navigation according to the requirements of the route it is possible to achieve significant fuel savings, reduce travel costs, increase energy efficiency and reduce environmentally harmful emissions of the ship.